Non-contrast Skeletal Muscle Oximetry - Jie, Zheng (2013)
PURPOSE: The objective of this study was to develop a new non-contrast method to directly quantify regional skeletal muscle oxygenation. METHODS: The feasibility of the method was examined in five healthy volunteers using a 3T clinical MRI scanner, at rest and during a sustained isometric contraction. The perfusion of skeletal muscle of the calf was measured using an arterial spin labeling method, whereas the oxygen extraction fraction of the muscle was measured using a susceptibility based MRI technique. RESULTS: In all volunteers, the perfusion in soleus muscle increased significantly from 6.5 ± 2.0 ml/100g/min at rest to 47.9 ± 7.7 ml/100g/min during exercise (P < 0.05). While the corresponding oxygen extraction fraction did not change significantly, the rate of oxygen consumption increased from 0.43 ± 0.13 to 4.2 ± 1.5 ml/100g/min (P < 0.05). Similar results were observed in gastrocnemius muscle, but with greater oxygen extraction fraction increase than the soleus muscle. CONCLUSION: This is the first MR oximetry developed for quantification of regional skeletal muscle oxygenation. A broad range of medical conditions could benefit from these techniques, including cardiology, gerontology, kinesiology, and physical therapy.